Advances in the Diagnosis of Latent Tuberculosis Infection - Schluger, Neil W. (Seminars in Respiratory and Critical Care Medicine, 2013)
Accurate diagnosis of tuberculosis (TB) infection is an important component of tuberculosis control programs in many countries. Identification of persons with asymptomatic, or latent, tuberculosis infection allows for treatment of individuals at high risk for progressing to active disease so that the overall burden of tuberculosis disease is diminished. In the United States, targeted testing and treatment of latent tuberculosis infection (LTI) are major components of the Centers for Disease Control and Prevention's efforts at TB elimination. This review focuses on the comparative utility of tuberculin skin testing and interferon-gamma release assays (IGRAs) to diagnose LTI. Commercially available IGRAs have superior sensitivity and specificity compared with conventional tuberculin skin testingin some settings (particularly bacille-Calmette Guérin–vaccinated individuals). Also discussed are the performance characteristics of these tests in specific populations, including foreign-born persons from high-prevalence countries, close contacts of actively infected patients, immunocompromised populations, and health care workers.
Keywords: tuberculosis; latent tuberculosis; tuberculin skin test; PPD; interferon gamma release assays; prophylaxis